IMPLIKASI BIOLOGICAL ASSET INTENSITY, UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL DAN KAP TERHADAP PENGUNGKAPAN ASET BIOLOGIS - Christopher Scarvino; Rustadi Rustadi; Melvie Paramitha; Chitra Santi (J-MACC, 2021)
Biological assets are assets of living animals or plants. One type of company that has biological assets is an agricultural company. The uniqueness of the characteristic that distinguishes biological assets from other assets is that biological assets are constantly undergoing biological transformation. Because of their uniqueness, biological assets need to be disclosed in the annual reports of agricultural companies based on the accounting standards contained in PSAK 69. This study aims to determine the effect of biological asset intensity, company size, managerial ownership, and Public Accounting Firm on the level of biological assets disclosure. The objects used in this research are agricultural companies listed on the IDX in 2018-2019. The population used in this study amounted to 26 agricultural companies. Meanwhile, the agricultural companies that were selected as samples were 21 companies which were determined based on purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that company size has a significant positive effect on the disclosure of biological assets. Meanwhile biological asset intensity, managerial ownership, and type of Public Accounting Firm have no effect on disclosure of biological assets.